2005
DOI: 10.1007/s00018-005-4523-7
|View full text |Cite
|
Sign up to set email alerts
|

Biomedicine and diseases: the Klippel-Trenaunay syndrome, vascular anomalies and vascular morphogenesis

Abstract: Vascular morphogenesis is a vital process for embryonic development, normal physiologic conditions (e.g. wound healing) and pathological processes (e.g. atherosclerosis, cancer). Genetic studies of vascular anomalies have led to identification of critical genes involved in vascular morphogenesis. A susceptibility gene, VG5Q (formally named AGGF1), was cloned for Klippel-Trenaunay syndrome (KTS). AGGF1 encodes a potent angiogenic factor, and KTS-associated mutations enhance angiogenic activity of AGGF1, definin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 106 publications
2
69
0
2
Order By: Relevance
“…It can either be congenital or acquired. The congenital form of angiomatosis may be seen sporadically or accompanying certain types of syndromes such as Klippel-Trenaunay-Weber syndrome, 5) Sneddon's syndrome, 6) or Gorham disease. 7) In these syndromes, the lesions may be observed in any tissue and are clinically extensive, covering large parts of the body in a continuous pattern.…”
Section: Discussionmentioning
confidence: 99%
“…It can either be congenital or acquired. The congenital form of angiomatosis may be seen sporadically or accompanying certain types of syndromes such as Klippel-Trenaunay-Weber syndrome, 5) Sneddon's syndrome, 6) or Gorham disease. 7) In these syndromes, the lesions may be observed in any tissue and are clinically extensive, covering large parts of the body in a continuous pattern.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is considered that thrombus formation is causally related to disturbance of mobility due to a prolonged bedridden state related to cerebral palsy from young childhood, especially due to paralysis of the lower extremities, which leads to contracture deformities of the lower extremities and concomitant narrowing of the vessels by vascular underdevelopment and immaturity. 22,23) Consequently, it has been suggested that thrombus forms in the conduct veins centrally in patients with SMID. We only detected it mainly in the common femoral and superficial veins, there were no associations with significantly elevated levels of D-dimer caused by reduced vessel volume due to vascular underdevelopment and immaturity.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that it may be associated with a translocation at (8;14) (q22.3;q13). Some researchers have suggested that VG5Q (Vasculogenesis gene on 5q protein) has an association (7)(8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%